1974
DOI: 10.1136/bmj.4.5940.316
|View full text |Cite
|
Sign up to set email alerts
|

Total Body Potassium in Long-Term Frusemide Therapy: Is Potassium Supplementation Necessary?

Abstract: whether "endogenous" or "reactive" need not concern us here-and that the disappearance of the compulsion is a direct consequence of the improvement in mood. We would need to examine a group of compulsive eaters who remained depressed after jejeunoileostomy to test this hypothesis and so far we have not found such a combination of features. Certainly, this explanation would be consistent with the conclusion that depression accompanying obesity is often consequential rather than causal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…In some instances a signifi cant body potassium depletion has been docu mented [2,[6][7][8][9], while in others body potassium was normal or only trivially reduced [3][4][5]10,11]. It is interesting and probably significant that the method of estimation of body potas sium content correlated closely to the observed findings.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In some instances a signifi cant body potassium depletion has been docu mented [2,[6][7][8][9], while in others body potassium was normal or only trivially reduced [3][4][5]10,11]. It is interesting and probably significant that the method of estimation of body potas sium content correlated closely to the observed findings.…”
Section: Discussionsupporting
confidence: 60%
“…It is interesting and probably significant that the method of estimation of body potas sium content correlated closely to the observed findings. With one exception [5], all the studies [2,[6][7][8][9] which utilized whole body radioisotope dilution technic with 42K (total exchangeable potassium) showed a significant body potas sium depletion, while those studies which uti lized whole body radioisotope counter and measured total body potassium revealed no significant depletion [3,4,10,11], The results of the present study adhere to that trend; our data were obtained by using the whole body counter and they showed no significant deple tion of potassium in the group as a whole. The disparity between the two sets of results ob tained in studies of similar populations seems then to be technical rather than one based on pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to determine and compare the prevalences of hypokalemia in geriatric patients taking diuretics alone or in combination with potassium supplements. Diuretics and aging have both been associated with potassium loss 11,12 ; however, it has also been found that potassium supplements are not consistently effective 13 . In our study the overall prevalence of hypokalemia in 161 geriatric patients residing in seven long‐term care facilities was 13.7 percent.…”
Section: Discussionmentioning
confidence: 53%
“…Dargie et al (1974) showed that patients with essential hypertension and normal renal function, who had been on 40 mg frusemide daily with or without potassium supplementation, showed no evidence of depletion of total body potassium.…”
Section: Discussionmentioning
confidence: 99%